PENGARUH PENERAPAN TEKNOLOGI INFORMASI TERHADAP EFISIENSI PENCATATAN AKUNTANSI PADA KOPERASI/UMKM - Adhwa Naifah Kamilla; Amelia Rahmawati; Dinda Mutaqin; Faradilla Eka Cahyani Putri; Kayla Ramadhani Putri Jodiansyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of information technology implementation on the efficiency of accounting record-keeping in cooperatives and micro, small, and medium enterprises (MSMEs) in the digital era. The background of this research arises from the fact that many cooperatives still use manual accounting systems, which often lead to problems such as recording errors, delayed financial reports, data duplication, and a lack of transparency in financial management. The adoption of information technology is considered an effective solution to these challenges by providing computerized accounting systems that are more efficient, accurate, and reliable. This study applies a descriptive qualitative method through a literature review approach, using secondary data from books, academic journals, and previous studies. The results show that the use of information technology has a positive impact on improving accounting efficiency by accelerating transaction processes, reducing human error risks, and enhancing the accuracy and reliability of financial reports. Furthermore, accounting digitalization strengthens internal control systems and facilitates real-time reporting. Therefore, information technology plays a crucial role in building professional, transparent, and competitive cooperatives within the growing digital economy.